Design And Development Of Learning Applications For Special Needs Students Using Android Studio (Case Study: Slb-Bc Yplab) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Education is the fundamental key in the process of understanding and comprehending a subject. Special needs children are children who have special characteristics compared to children in general. One type of special needs children is children with an intellectual disability or often called mentally retarded children. The use of technology can also be applied as a medium, a means that can be used in the form of interesting videos and exercises where both of them are methods and keys for children’s learning. By employing Android Studio as the learning method, it can create an interesting and entertaining learning atmosphere for mentally retarded children.